2017
DOI: 10.1155/2017/6895928
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Al2O3, CaO/SiO2, and B2O3 on Viscous Behavior of High Alumina and Medium Titania Blast Furnace Slag

Abstract: on the viscosity of high alumina and medium titania blast furnace slag was analyzed. An increase in CaO/SiO 2 ratio from 1.14 to 1.44 resulted in higher slag viscosity and break point temperature. They also increased with increasing Al 2 O 3 content but decreased with adding B 2 O 3 and Al 2 O 3 simultaneously at a fixed CaO/SiO 2 ratio of 1.14, which suggested that the effect of B 2 O 3 on viscosity and break point temperature is predominant compared to Al 2 O 3 . Apparent activation energies of CaO-SiO 2 -Mg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 28 publications
0
8
0
Order By: Relevance
“…The viscosity of CaO-MgO-Al 2 O 3 -SiO 2 -TiO 2 system has been investigated by many researchers [10][11][12][13][14][15][16][17][18][19][20][21][22][23][24].There has been a consensus among the studies [11][12][13][14][15][16][17][18] that TiO 2 was a reducing viscosity agent in the quinary slag with fixed MgO, Al 2 O 3 and basicity. For the effect of binary basicity, most experts reported that viscosity decreased with increasing basicity [17][18][19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The viscosity of CaO-MgO-Al 2 O 3 -SiO 2 -TiO 2 system has been investigated by many researchers [10][11][12][13][14][15][16][17][18][19][20][21][22][23][24].There has been a consensus among the studies [11][12][13][14][15][16][17][18] that TiO 2 was a reducing viscosity agent in the quinary slag with fixed MgO, Al 2 O 3 and basicity. For the effect of binary basicity, most experts reported that viscosity decreased with increasing basicity [17][18][19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…For the effect of binary basicity, most experts reported that viscosity decreased with increasing basicity [17][18][19][20][21][22]. There was also a different view that higher basicity led to higher slag viscosity in the high alumina and medium titania BF slag [23]. Considering the influences of MgO and Al 2 O 3 , it was believed that the addition of MgO content can decrease viscosity [13,20,21].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The reduction of either F or CaF 2 results in a drastic increase in the viscosity of the remaining liquid [24]. Moreover, the increase of Al 2 O 3 also causes the significant surge in viscosity [25]. The solute diffusivity in the liquid phase is inversely proportional to the viscosity according to the Stokes-Einstein equation as…”
Section: Formation Of Sub-bandsmentioning
confidence: 99%
“…The final slag is usually described by a CaO−MgO−Al 2 O 3 −SiO 2 −TiO 2 quinary system, which has been researched in many experimental studies [3][4][5][6][7][8][9] about the effects of MgO and Al 2 O 3 on slag viscosity. The effect of Al 2 O 3 content on the viscosity of quinary slag with different TiO 2 concentrations was studied by Feng et al [3], Yan et al [4], and Bian and Gao [5]. All the results showed that Al 2 O 3 increased viscosity, which was attributed to the role of Al 2 O 3 in the polymerization of silicate melts [10,11].…”
Section: Introductionmentioning
confidence: 99%